Study of Safety of Medicinal Products in Pregnant Women in Crimea - A. V. Matveev; E. A. Egorova; A. E. Krasheninnikov; E. I. Konyaeva (Безопасность и риск фармакотерапии)
According to international epidemiological studies, about 80% of women have to use medicinal products during pregnancy, mainly during the ﬁrst weeks of organogenesis in the case of an unplanned pregnancy, and for the treatment of chronic diseases or acute conditions developing during pregnancy. Speciﬁcity of pharmacokinetics and pharmacodynamics in pregnant women contributes to the development of adverse drug reactions (ADRs), many of which are serious and pose a threat to the life of the patient. The aim of the study was to retrospectively assess the frequency and development of ADRs in pregnant women living in the Republic of Crimea, based on the data in the regional safety database ARCADe (Adverse Reactions in Crimea, Autonomic Database). Materials and methods: the authors analysed spontaneous ADR reports registered in the ARCADe database from 1 January 2009 until 31 December 2018 for the category of patients described as “Pregnant women/childbirth”. Results: during the speciﬁed period, 268 ADR cases in pregnant women were added to the database. The most common reasons of ADRs in this category of patients were antibacterials for systemic use (130 cases, 48.5%), agents that have an eﬀect on haematopoiesis and blood (54 cases, 20.15%), and agents that have an eﬀect on the functions of the gastrointestinal tract (29 cases, 10.82%). The study of ADR clinical manifestations revealed a high incidence of local allergic reactions (140 cases, 52.2%), inhibition of haematopoiesis (60 cases, 22.4%), and dyspepsia (36 cases, 13.4%). The analysis of the severity of the registered ADRs demonstrated that in 15 cases (5.6%) the use of the prescribed medicinal product posed a threat to the patient’s life and required urgent pharmacotherapy and discontinuation of the suspected medicine, in 8 cases (3%) it resulted in hospitalisation or prolongation of hospital treatment, and in 3 cases (1.12%) it resulted in the temporary inability to work. Conclusions: the results of the study indicate the need for further retrospective and prospective studies aimed at analysing the safety of medicine use in pregnant women and assessing the risks of toxic eﬀects on the foetus.